Comparison of the volatile organic compounds in Citrus reticulata ‘Chachi’ peel with different drying methods using E-nose, GC-IMS and HS-SPME-GC-MS - Wang, Min; Li, Xue; Ding, Haiyan; Chen, Hongping; Liu, Youping; Wang, Fu; Chen, Lin (Frontiers in Plant Science, 2023)
Citrus reticulata ‵Chachi′ peel (CRCP), which is named ‶Guangchenpi″ in China, is a geographical indication product with unique flavor properties. CRCP has been used for centuries as a traditional genuine herb because of its excellent therapeutic effects. In addition, owing to its unique odor and high nutrition, it is widely used in various food preparations. Volatile organic compounds (VOCs) are regarded as an important quality marker for CRCP and are highly susceptible to effects in the drying process due to their thermal instability. In the current study, the main VOCs in CRCP were processed using different drying methods, including sun-drying, hot air drying, and vacuum-freeze drying. The VOCs were identified by the electronic nose (E-nose), gas chromatography-ion mobility spectrometry (GC-IMS), and headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS). The results showed that the CRCP dried by vacuum-freeze exhibited the highest VOCs contents and retained the richest compounds compared to those dried by other methods, which indicated that vacuum-freeze drying is the most suitable for CRCP production. Furthermore, the chemometrics analysis revealed that the primary differential metabolites of the samples generated using different drying methods were terpenes and esters. Overall, our study would help better understand the VOCs present in CRCP with different drying methods. The outcomes of the current study would guide the drying and processing of CRCP, which is beneficial for large-scale storage and industrial production of CRCP.